Exploring the epidemiological characteristics of Mpox in the Arab Gulf countries - Yehya M. Althobaity; Michael J. Tildesley (Scientific Reports)
Abstract In May 2022, Mpox outbreaks emerged in regions where the virus is not traditionally prevalent. This study estimates the mean incubation period, serial interval and the extent of presymptomatic transmission in the Arab Gulf Countries (AGC). The effective reproduction number ( $$R_e$$ ) is also calculated, as well as the degree of heterogeneity ( $$K$$ ), using the instant-individual heterogeneity transmission model. We analyze data from 41 confirmed cases for which we have complete information, estimating the mean incubation period using gamma, Weibull and lognormal distributions, with respective means of 8.52 (95% CI 7.26–9.98), 8.57 (95% CI 7.28–10.01), and 8.64 (95% CI 7.23–10.26) days. The mean serial interval, based on 31 case pairs, was 7.19 days (95% CI 4.11–12.95), 7.16 days (95% CI 5.80–8.90), and 10.0 days (95% CI 6.30–16.3) for the gamma, Weibull, and lognormal distributions, respectively. The Akaike Information Criterion (AIC) validated the best-fitting models. The serial intervals were shorter than the incubation periods, suggesting that pre-symptomatic transmission occurred in 60% of transmission events. We estimated $$R_e$$ to be 0.95 (95% highest posterior density [HPD]: 0.93–1.35) and $$K$$ to be 1.52 (95% HPD: 1.07–5.76), indicating supercritical Mpox transmission in the AGC with limited transmission heterogeneity. Using a Bayesian framework with non-informative priors and a negative binomial distribution, we projected $$R_e$$ to remain between 0.95 and 1.0 from August 2022 to January 2023, underscoring the need for continued efforts to reduce transmissibility. These findings provide valuable information for public health interventions, emphasizing a multifaceted approach to managing Mpox transmission.